Neonatal Outcomes of Immigrant and Turkish Preterm Infants Treated in a Level-3 Neonatal Intensive Care Unit: A Retrospective Study - Nuriye Tarakçı; Fatma Hilal Yılmaz; Hüseyin Altunhan (Galenos Yayinevi, 2021)
Aim:To evaluate the neonatal outcomes of immigrant preterm babies and compare them with Turkish preterm babies in a Neonatal Intensive Care Unit (NICU).Materials and Methods:The present study was conducted using a retrospective design in the NICU of Necmettin Erbakan University between October 2015 and October 2019. Antenatal, natal and postnatal outcomes of the premature infants were evaluated and compared.Results:Maternal age (p<0.001), antenatal follow-up (p<0.001), antenatal steroid use (p<0.001), patent ductus arteriosus (PDA) (p=0.03) and bronchopulmonary dysplasia (BPD) (p=0.05) were statistically higher in the Turkish patients. Additionally, the rates of breastfeeding (p<0.01) and kangaroo mother care (p<0.01) were found to be higher among Turkish mothers. On the other hand, the necrotizing enterocolitis (NEC) rate (p=0.002) was found to be higher among immigrant babies. Duration of mechanical ventilation and oxygen supply were similar for both groups; however, the duration of nasal-continuous positive airway pressure use was longer in the Turkish patients (p=0.01).Conclusion:In this study, immigrant mothers were younger than their Turkish counterparts and their antenatal follow-ups were insufficient. The rate of hospitalization in a NICU and NEC rates were higher in immigrant preterm infants, respiratory distress syndrome, PDA and BPD were more commonly encountered in Turkish preterm infants.